PERSEPSI GURU TERHADAP IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI SEKOLAH DASAR - Fiana Saphira; Mery Hardianty; Sumiyati; M. Iqbal Arrosyad (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research began with the observation of a significant discrepancy between expectations regarding the Independent Curriculum and the implementation of differentiation in classroom teaching. The purpose of this study is to describe teachers' perceptions of the implementation of the independent learning curriculum in elementary schools.The method used in this research was a qualitative case study design. Data collection techniques included participant observation, in-depth interviews, and document analysis, aimed at comprehensively understanding differentiation practices within their context. The primary focus of this research was on classroom teachers implementing the Independent Curriculum. This research was conducted at SD Negeri 24 Pangkal Pinang and implemented in 2 October 2025. The results indicated that the implementation of differentiation in content, process, and product still faced various challenges, particularly in terms of time management, limited resources, and teachers' ability to conduct accurate diagnostic assessments. Strategies deemed effective included ongoing training, collaboration between teachers, and the use of technology to personalize the learning process. This study also recommended that schools implement policies supporting the provision of time and professional development for teachers directly related to differentiation.